PENGEMBANGAN MEDIA FLASHCARD BERBASIS LITERASI UNTUK MELATIH KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK KELAS I SEKOLAH DASAR - Rosanti, Sri; Yuliana, Rina; Tisnasari, Sundawati (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to describe the development, feasibility, and student responses toward literacy-based flashcard media as a learning tool to improve early reading skills among first-grade students. The research employed a Research and Development (R&D) approach adapted from the Borg and Gall model, which consisted of six stages. The subjects of this study were first-grade students. Data were collected through interviews, questionnaires, and documentation. The results of the study show that: (1) the average score from media experts was 69.33%, categorized as “Feasible”; (2) the average score from material experts was 94.15%, categorized as “Highly Feasible”; (3) the average score from language experts was 95%, categorized as “Highly Feasible”; and (4) the average student response score was 89%, categorized as “Very Good.” Based on these findings, it can be concluded that the literacy-based flashcard media is feasible to use and can serve as an effective teaching aid to develop early reading skills among elementary school students.